From extra-mural to knowledge transfer partnerships and networking: The community engagement experience at Makerere University - Openjuru, George Ladaah; Ikoja-Odongo, John Robert (Perspective, Prospects and Challenges, NIACE, London., 2012)
Community engagement/services, outreach activities or extra-mural services are a core function of all universities. According to Atim (2004), the history of these services in Makerere University dates back to 1953 with the formation of the Department of Extra-Mural Studies to help prepare the country for independence. This combination of services remains a core function but is now one of the strategic goals and objectives of the university, based on its vision and mission (Makerere University, 2008a). Makerere University is unusual in that it can demonstrate some university-wide strategies and structures to promote this work.